2006
DOI: 10.1111/j.1365-2966.2006.11101.x
|View full text |Cite
|
Sign up to set email alerts
|

The 6C** sample of steep-spectrum radio sources – I. Radio data, near-infrared imaging and optical spectroscopy

Abstract: We present basic observational data on the 6C** sample. This is a new sample of radio sources drawn from the 151‐MHz 6C survey, which was filtered with radio criteria chosen to optimize the chances of finding radio galaxies at z > 4. The filtering criteria are a steep‐spectral index and a small angular size. The final sample consists of 68 sources from a region of sky covering 0.421 sr. We present Very Large Array radio maps, and the results of K‐band imaging and optical spectroscopy. Near‐infrared counterpart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
0
32
1
Order By: Relevance
“…4) it is located at the separation between quasars and galaxies. 0810+460B: identification and redshift from Cruz et al (2006) 8) shows a low level of excitation consistent with a shock heating mechanism. 0822+394: a photometric redshift z = 1.18 (1.0-1.4) is reported by Lilly (1989); (in a note z ≈ 1.2 is given).…”
Section: Discussionmentioning
confidence: 99%
“…4) it is located at the separation between quasars and galaxies. 0810+460B: identification and redshift from Cruz et al (2006) 8) shows a low level of excitation consistent with a shock heating mechanism. 0822+394: a photometric redshift z = 1.18 (1.0-1.4) is reported by Lilly (1989); (in a note z ≈ 1.2 is given).…”
Section: Discussionmentioning
confidence: 99%
“…There are suggestions that the USS method is more efficient in selecting high-z sources at the flux density limit of approximately 10 mJy at 1.4 GHz, while the fraction of high-z sources decreases at lower and higher flux densities (e.g., Dunlop & Peacock 1990;Best et al 2003). In the literature, many studies of the USS samples have also used additional selection criteria such as small angular size and faint infrared magnitude to select high-z sources (De Breuck et al 2004;De Breuck et al 2006;Cruz et al 2006). According to the K−z relation, HzRGs are expected to be faint in K-band and indeed, several HzRGs have been discovered by pre-selecting them in K-band (Jarvis et al 2001b;Brookes et al 2006;Jarvis et al 2009).…”
Section: High-z Radio Sources In Faint Uss Samplementioning
confidence: 99%
“…The correlation between the steepness of the radio spectrum and cosmological redshift (i.e., z − α correlation) has been used as one of the successful tracers to find HzRGs (Roettgering et al 1994;Chambers et al 1996;De Breuck et al 2000, 2002aKlamer et al 2006;Ishwara-Chandra et al 2010;Ker et al 2012). Most of the radio galaxies known at z > 3.5 have been found using the ultra steep spectrum (USS) criterion (Blundell et al 1998;De Breuck et al 1998, 2000, 2002bJarvis et al 2001aJarvis et al ,b, 2004Cruz et al 2006;Miley & De Breuck 2008). The causal connection between the steepness of radio spectral index and redshift is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…151 < −0.981 (Blundell et al 1998), α 325 74 < −1.2 ), α 1400 843 < −1.3 , α 1400 151 < −1.0 (Cruz et al 2006), α 843 408 < −1.0 (Broderick et al 2007). In this work we have adopted a selection based on a conservative value of α 1400 610 ≤ −1.3, which results in a sample of 65 USS sources, 10 of which are not detected at 1.4 GHz (i.e.…”
Section: Uss Sample Selectionmentioning
confidence: 99%
“…Although an ultra-steep (radio) spectrum (USS; α −1 with S ∝ ν α ) does not guarantee a high redshift, and the USS selection may actually miss a large fraction of HzRGs (e.g. Waddington et al 1999;Jarvis et al 2001cJarvis et al , 2009), a higher fraction of high-redshift sources can be found among those with the steepest radio spectra, and most of the radio galaxies known at z > 3.5 have been found using the USS criterion (Blundell et al 1998;De Breuck et al 1998Jarvis et al 2001a,b;De Breuck et al 2002a;Jarvis et al 2004;Cruz et al 2006;Miley & De Breuck 2008). A satisfactory explanation for this trend is still missing.…”
Section: Introductionmentioning
confidence: 99%